Profile of health and oral diseases in population from 6 to 18 years from San Juan de Miraflores district, of Lima Department 2010 - Vilchez Salazar, Ernesto Fidel (2012)
The aim of this epidemiological, descriptive and cross sectional study, was to determine oral health-disease profile among 6-18 years old population in the district of San Juan de Miraflores, Lima. Sample were 160 students from four schools: three public and one private school: 79 men and 81 women. The results were: 75.4 % of caries prevalence and DMFT were 4.8, being higher in women. Hypoplasia had 11.8 %, and it was more prevalent in women; poor oral hygiene had 61.9 % and it was more prevalent in women too; had bleeding periodontal status 55 % more prevalent in men; had slight malocclusion 50.1 % more prevalent in men; had mucosal injury 9.8 %. Oral deseases were related to socioeconomic condition being more prevalent in extremely poverty and poor people.